2023
DOI: 10.1021/acsapm.3c01656
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic-Framework-Based Polymers for Effective Water Harvesting in Arid Areas

Xiaomei Liu,
Tao Feng,
Wenbin Ding
et al.

Abstract: This study used a postsynthetic modification strategy to amidate UIO-66-NH2 to synthesize a functional copolymer monomer by free radical polymerization with acrylic acid (AA) and acrylamide (AM) to form hygroscopic polymer materials based on UIO-66-NH2 (UPHMs). The experiments show that the uptake capacity of UIO-66-NH2-self-polymerization products and UPHMs for water vapor is 11.1 and 18.6 times that of pure UIO-66-NH2, respectively. And UPHMs can be adsorbed in a wide range of adsorption humidity (relative h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Chitosan, as a polymer with cationic polysaccharide, has been developed for water-related applications, , owing to favorable biocompatibility, biodegradability, antibacterial properties, water treatment by complexing and adsorbing pollutants, , and immense potential for AWH. , Abundant functional groups (−NH 2 and −OH) exist on the chitosan chain, which is conducive to form the porous structure as water adsorbent. Chitosan skeleton to be combined with MOFs also endows composites with multifunctionality via electrostatic interaction and hydrogen bonding, e.g., designed as an efficient water evaporator, porous gels, and MOF-based AWH materials. , Although so, most MOF-based AWH materials show water adsorption at relatively high humidity (e.g., 30–90%), water released under strong light irradiation with high heat (e.g., 50–80 °C), along with low efficiency. Up to now, although much research on atmospheric water harvesting has been reported, it is still challenging to develop a robust atmospheric water harvester with ultrahigh uptake-release efficiency at extremely low relative humidity (e.g., RH < 30%).…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan, as a polymer with cationic polysaccharide, has been developed for water-related applications, , owing to favorable biocompatibility, biodegradability, antibacterial properties, water treatment by complexing and adsorbing pollutants, , and immense potential for AWH. , Abundant functional groups (−NH 2 and −OH) exist on the chitosan chain, which is conducive to form the porous structure as water adsorbent. Chitosan skeleton to be combined with MOFs also endows composites with multifunctionality via electrostatic interaction and hydrogen bonding, e.g., designed as an efficient water evaporator, porous gels, and MOF-based AWH materials. , Although so, most MOF-based AWH materials show water adsorption at relatively high humidity (e.g., 30–90%), water released under strong light irradiation with high heat (e.g., 50–80 °C), along with low efficiency. Up to now, although much research on atmospheric water harvesting has been reported, it is still challenging to develop a robust atmospheric water harvester with ultrahigh uptake-release efficiency at extremely low relative humidity (e.g., RH < 30%).…”
Section: Introductionmentioning
confidence: 99%